IMPLEMENTATION OF THE USE OF INVENTORY STOCK CARDS (Case Study on Small Businesses in Kotaraja, Jayapura City) - Y. Flora Hosio; Novalia H. Bleskadit; Chelvin Rumbiak; Maikel Yalehatu; Sobert Sandang (RADJA PUBLIKA, 2025)
Community service for small businesses is not limited to bookkeeping alone, but also to inventory recording for small businesses as a form of responsibility from the university to the surrounding community. This is due to the problem of poorly organized inventory recording. Many products are sold, but unstructured inventory recording often results in discrepancies. Furthermore, inaccurate recording also results in unorganized records, requiring traders to double-check when purchasing or searching for stock. This Community Service Program (PKM) activity consists of identification, planning, implementation, evaluation, and documentation. After evaluation, all stages resulted in three successful implementations of inventory stock card recording: inventory efficiency, which is the ability to maintain inventory below a certain limit, and others.